2022
DOI: 10.3389/fneur.2022.859276
|View full text |Cite
|
Sign up to set email alerts
|

Relatively Early and Late-Onset Neuromyelitis Optica Spectrum Disorder in Central China: Clinical Characteristics and Prognostic Features

Abstract: BackgroundWe aimed to analyze the clinical characteristics and prognostic features of Chinese patients with relatively late-onset neuromyelitis optica spectrum disorder (RLO-NMOSD>40 years of age at disease onset), compared with patients with relatively early onset NMOSD (REO-NMOSD, ≤ 40 years of age at disease onset).MethodsWe retrospectively reviewed the medical records of patients with NMOSD in central China (with disease courses longer than 3 years) between January 2012 and January 2021. We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…Worse prognosis and severer motor disability in LO-NMOSD have been demonstrated in several previous studies ( 5 8 , 17 , 25 , 28 , 29 ), as well as in the present study: the EDSS score at last follow-up increases with onset age; older age at disease onset predict motor disability and severe disability at last follow-up; patients with older age of onset progress to motor disability more quickly. The reasons for worse prognosis in LO-NMOSD were unclear yet.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Worse prognosis and severer motor disability in LO-NMOSD have been demonstrated in several previous studies ( 5 8 , 17 , 25 , 28 , 29 ), as well as in the present study: the EDSS score at last follow-up increases with onset age; older age at disease onset predict motor disability and severe disability at last follow-up; patients with older age of onset progress to motor disability more quickly. The reasons for worse prognosis in LO-NMOSD were unclear yet.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, several studies showed similar relapsing rate between LO-NMOSD and EO-NMOSD measured by ARR ( 6 , 8 ). It is proposed that ARR-1 may be more accurate to avoid inappropriately high ARR values in patients with disease duration less than 1 year ( 5 , 8 , 27 , 28 ). In line with this, ARR was not significantly correlated with onset age in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation